CLUSTER THEORY AND DEVELOPMENT OF AGROCLUSTERS IN THE REPUBLIC OF UZBEKISTAN - Hafizov Bunyodjon Zayniddin o’g’li (Galaxy International Interdisciplinary Research Journal, 2021)
This article presents various theories of the formation and development of clusters. The state of development of agroclusters has been studied on the examples of created agroclusters in the Republic of Uzbekistan. There are given the main directions for the creation and development of agricultural clusters in the country.